Annalisa and the witch fairy - Aqil, Emaan (Lahore : Check mate publisher)
Brace yourself for an adventure with Annalisa as with a dream. a splash of a mermaid tale and a flutter of fairy wings bring her face to face with the most chaotic, brutal witch of all times who wants the impossible. You've guessed it! Annalisa and the witch depart on the most threatening journey ever attempted or heard of. The witch is off to prove that she is worthy of becoming a fairy......
Location: 3B
Keywords: Story book